"Are trans men the manliest of men?" Gender practices, trans masculinity and mardānegī in contemporary Iran. Issue 3 (2nd April 2020) - Saeidzadeh, Zara
ABSTRACT: In this article, I examine how trans men who undergo or plan to undergo medical transition construe their masculinity or mardānegī (I follow IJMES's transliteration guide – Persian to English) in Persian language, through certain gender practices that manifest their manhood as manly, real and psychologically well. I argue that trans men in Iran practice masculinity in ways that is not only in strong entanglement with women but also is distanced from non-trans heterosexual men, trans women and gay men. Drawing on 14 semi-structured interviews with trans men in Iran as part of a bigger project on sex change in contemporary Iran, I explain that trans men's masculinity in Iran is a localized, traditional-modern kind of trans masculinity that distinguishes itself from other gender groups due to trans men's specificity of gender location.